2023
DOI: 10.1096/fj.202201523r
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of melatonin‐mediated mitophagy through nucleotide‐binding oligomerization domain and leucine‐rich repeat‐containing protein X1 in neonatal hypoxic–ischemic brain damage

Abstract: Hypoxia–ischemia (HI) is a major cause of brain damage in neonates. Mitochondrial dysfunction acts as a hub for a broad spectrum of signaling events, culminating in cell death triggered by HI. A neuroprotective role of melatonin (MT) has been proposed, and mitophagy regulation seems to be important for cell survival. However, the molecular mechanisms underlying MT‐mediated mitophagy during HI treatment are poorly defined. Nucleotide‐binding oligomerization domain and leucine‐rich repeat‐containing protein X1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The cells were pre-incubated with the tested compounds at concentrations 1, 10, and 20 µM for 90 min. Melatonin was used as a reference compound because of its well-established neuroprotective effects in various in vitro and in vivo models [ 17 ]. After 90 min pre-incubation with the test substances, SH-SY5Y cells were exposed to H 2 O 2 (1 mM, 15 min), as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were pre-incubated with the tested compounds at concentrations 1, 10, and 20 µM for 90 min. Melatonin was used as a reference compound because of its well-established neuroprotective effects in various in vitro and in vivo models [ 17 ]. After 90 min pre-incubation with the test substances, SH-SY5Y cells were exposed to H 2 O 2 (1 mM, 15 min), as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that MT exerts its protective effects on the nervous system by inducing mitophagy. In a neonatal hypoxic-ischemic encephalopathy model, intraperitoneal injection of MT (15 mg/kg) into pups 1 h before hypoxia induction upregulated the expression of NLRX1, which downregulated mTOR expression and promoted ATG7 and Beclin-1 expression to promote mitophagy and inhibit apoptosis [46]. In a model of glutamate-induced cytotoxicity in mouse hippocampal neurons, pretreatment with 10 −7 mol/L MT for 2 h mediated mitophagy via the Beclin-1/Bcl-2 pathway, thus exerting antioxidative stress and neuroprotective effects [47].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial biosynthesis and mitochondrial autophagy flow after injury are the key links in the repair of renal tubular injury. NLRX1 is a member of the NLR family, which plays an important role in regulating immune response, promoting ROS production, mitochondrial damage, autophagy, [12] apoptosis [13] and so on. Because the N-terminal of NLRX1 contains a mitochondrial localization sequence, it becomes the first NLR located in mitochondria and plays an important role in mitochondrial directional transmission.…”
Section: Inflammatory Body Signal Pathway Influenced By Nlr Familymentioning
confidence: 99%